2008
DOI: 10.1016/j.tsf.2008.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Inductively coupled plasma etching of nano-patterned sapphire for flip-chip GaN light emitting diode applications

Abstract: The flip-chip configuration is employed for the production of high-brightness GaN-based light emitting diodes to improve the extraction of heat. A lithographic approach based on a sacrificial SiO 2 nanosphere etch mask was developed to enhance the external extraction of light from the sapphire substrate. Closed-packed arrays of SiO 2 nanospheres were prepared by a simple solution-based method on the sapphire substrate. Subsequent dry-etching via inductively coupled plasma using a gas mixture of BCl 3 and Cl 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Emerging system-in-package and three-dimensional (3D) integration technologies [1][2][3][4] are the predominant providers of solutions for miniaturizing systemized radio frequency or millimeter wave devices. Previous research [5] reported the development of an inkjet-printed folded-bowtie radio frequency identification tag module on a paper substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging system-in-package and three-dimensional (3D) integration technologies [1][2][3][4] are the predominant providers of solutions for miniaturizing systemized radio frequency or millimeter wave devices. Previous research [5] reported the development of an inkjet-printed folded-bowtie radio frequency identification tag module on a paper substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the dimensions of a photonic crystal designed for a GaN-based emitter are on the order of 250 nm [5], which is difficult to implement in a highvolume lithography process e although self-assembled approaches have proven promising [6]. A much simpler manufacturing approach is to roughen the GaN surface or the sapphire substrate (in a flip-chip configuration) to create an ensemble of sub-micron scattering sites [7]. A recent variant of this approach is to roughen the surface of the sapphire substrate prior to growth [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many research teams have attempted to improve LEE by roughening LED, in which the method of wet etching, dry etching and haze film has generally been used. [7][8][9][10][11][12][13] The aforementioned studies successfully enhanced FC LED efficiency by roughening sapphires. However, in actual industrial productions, sapphire substrates of FC LED must be thinned to 150 µm before they can be made into a surface structure.…”
mentioning
confidence: 99%